THE IMPACT OF COVID 19 ON NATIONAL ECONOMIC GROWTH - Aliah, Nur (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
The spread of this virus has resulted in all parts of the world experiencing shocks both mentally and economically. Indonesia is one of the countries that is feeling the bad impact of the spread of COVID-19. Since it was first reported on March 2, 2020, the number of COVID-19 cases in Indonesia has continued to increase. The policies issued by the government have resulted in decreased economic activity thus affecting national economic growth. Slowing Exports of Goods and commodity prices and declining exports of tourism services were one of the factors that slowed the national economic growth.The policies issued by the government to deal with the spread of the COVID-19 virus resulted in many industries going out of business and having to do Termination of Employment (PHK). This has an impact on increasing unemployment in Indonesia which is in line with the decline in the income of the Indonesian people